Sound, Speech, Music in Soviet and Post-Soviet Cinema - Salazkina, Masha; Kaganovsky, Lilya (Book collections on Project MUSE., 2014)
This innovative volume challenges the ways we look at both cinema and cultural history by shifting the focus from the centrality of the visual and the literary toward the recognition of acoustic culture as formative of the Soviet and post-Soviet experience. Leading experts and emerging scholars from film studies, musicology, music theory, history, and cultural studies examine the importance of sound in Russian, Soviet, and post-Soviet cinema from a wide range of interdisciplinary perspectives. Addressing the little-known theoretical and artistic experimentation with sound in Soviet cinema.